Regulation of nucleosome positioning by a CHD Type III chromatin remodeler and its relationship to developmental gene expression in Dictyostelium - Platt, James L.; Kent, Nicholas A.; Kimmel, Alan R.; Harwood, Adrian J. (Genome Research, 2017)
Nucleosome placement and repositioning can direct transcription of individual genes; however, the precise interactions of these events are complex and largely unresolved at the whole-genome level. The Chromodomain-Helicase-DNA binding (CHD) Type III proteins are a subfamily of SWI2/SNF2 proteins that control nucleosome positioning and are associated with several complex human disorders, including CHARGE syndrome and autism. Type III CHDs are required for multicellular development of animals and Dictyostelium but are absent in plants and yeast. These CHDs can mediate nucleosome translocation in vitro, but their in vivo mechanism is unknown. Here, we use genome-wide analysis of nucleosome positioning and transcription profiling to investigate the in vivo relationship between nucleosome positioning and gene expression during development of wild-type (WT) Dictyostelium and mutant cells lacking ChdC, a Type III CHD protein ortholog. We demonstrate major nucleosome positional changes associated with developmental gene regulation in WT. Loss of chdC caused an increase of intragenic nucleosome spacing and misregulation of gene expression, affecting ∼50% of the genes that are repositioned during WT development. These analyses demonstrate active nucleosome repositioning during Dictyostelium multicellular development, establish an in vivo function of CHD Type III chromatin remodeling proteins in this process, and reveal the detailed relationship between nucleosome positioning and gene regulation, as cells transition between developmental states.